Acquired Coagulopathy and Hemorrhage Secondary to Subcutaneous Heparin Prophylaxis - Maria Sunseri; Tania Ahuja; Tanya Wilcox; David Green (Case Reports in Hematology)
Unfractionated heparin and low-molecular-weight heparins are commonly used as thromboprophylaxis for hospitalized patients. Though generally considered safe at prophylactic doses, cases of catastrophic hemorrhage have been reported. The proposed mechanism involves bioaccumulation of heparin through saturation of the rapid-elimination pathway in its metabolism. We present an unusual case of an average-weight man with metastatic melanoma who suffered hemorrhage with syncope and end-organ damage while on prophylactic three times daily unfractionated heparin. Coagulation studies were consistent with heparin toxicity. Despite administration of protamine, the clearance of heparin was remarkably delayed, as demonstrated by serial coagulation studies. We review the suspected risk factors for heparin bioaccumulation and the emerging understanding of this unusual adverse event involving a nearly ubiquitous medication.